2013
DOI: 10.1038/nrg3606
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs: new players in cell differentiation and development

Abstract: Genomes of multicellular organisms are characterized by the pervasive expression of different types of non-coding RNAs (ncRNAs). Long ncRNAs (lncRNAs) belong to a novel heterogeneous class of ncRNAs that includes thousands of different species. lncRNAs have crucial roles in gene expression control during both developmental and differentiation processes, and the number of lncRNA species increases in genomes of developmentally complex organisms, which highlights the importance of RNA-based levels of control in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
2,125
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 2,631 publications
(2,153 citation statements)
references
References 129 publications
20
2,125
0
8
Order By: Relevance
“…[7][8][9] Different from other RNAs, the ncRNAs demonstrate their indispensable biological function mostly in gene regulation during differential process, tumorigenesis and tumor progression. 10 According to the length of non-coding RNAs, several subgroups have been classified, including short ncRNAs, mid-size ncRNAs and long ncRNAs. Long ncRNAs (>200 nucleotides in size) comprise long intervening non-coding RNA (lincRNA), transcribed ultraconserved regions (T-UCRs) and ceRNAs.…”
Section: Classification Of Circrnasmentioning
confidence: 99%
“…[7][8][9] Different from other RNAs, the ncRNAs demonstrate their indispensable biological function mostly in gene regulation during differential process, tumorigenesis and tumor progression. 10 According to the length of non-coding RNAs, several subgroups have been classified, including short ncRNAs, mid-size ncRNAs and long ncRNAs. Long ncRNAs (>200 nucleotides in size) comprise long intervening non-coding RNA (lincRNA), transcribed ultraconserved regions (T-UCRs) and ceRNAs.…”
Section: Classification Of Circrnasmentioning
confidence: 99%
“…Although only a small number of functional long non-coding RNAs (lncRNAs) have been well characterized to date, they seem to control major biological processes impacting cell differentiation and development [1]. Specifically, recent work suggested that a large number of lncRNAs function to epigenetically modulate gene expression through interacting with chromatin modifiers or remodelers.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetically activated HOTAIRM1 can also negatively or positively affect the expression of its neighbouring genes. Indeed, previous studies have shown that HOTAIRM1 plays key roles in myeloid differentiation by cis‐ regulating the expression of neighbouring homeobox transcription factor A (HOXA) genes 30. Thus, it is possible for H3K4me3‐activated HOTAIRM1 to contribute to the development of GBM by enhancing the expression of neighbouring HOXA1, an oncogene present in several cancers.…”
Section: Epigenetic Control Of Lncrna Expressionmentioning
confidence: 99%